Labour Force Patterns And Self-Perceived Health Status Among Older Australians: Implications For Healthy Ageing - Kanjanapan, W (My University, 2002)
Using the data from the first wave of the Household Income and Labour Dynamics in Australia (HILDA) Survey conducted in 2001, this study examines differences in selfperceived health status among the employed and non-employed older adults. The results confirm what has been found in other developed countries that people in paid employment, including those in older age groups, have better health than those who are unemployed or are no longer in the labour force. A preliminary descriptive analysis suggests that this association between employment in later life and positive self-assessed health status may have a more complex relationship to health risk behaviours such as smoking and physical inactivity than may have been anticipated. Social relationships and self-rated economic wellbeing are also found to play an important role in the complex relationship between work in later life and health. Policy implications for healthy and successful ageing are discussed.
Keywords: Health; Employment -- Labour force status and attachment; Employment; Health and wellbeing; Labour market; Health; Employment and unemployment